تقلبات سعر صرف الدولار وأثرها على التجارة الخارجية للجزائر في ظل تذبذب أسعار البترول خلال الفترة 2004_2014 - بن سمينة, عزيزة (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 02 (2016): مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
يمثل سعر الصرف أحد أهم المتغيرات المؤثرة على التجارة الخارجية لمختلف الدول، فالتحولات الاقتصادية الدولية وضعت العديد من الدول خاصة النامية منها أمام تحديات تفرض عليها مراجعة سياستها المالية والنقدية وتكييفها مع مختلف التقلبات الحاصلة على الساحة الدولية حماية لاقتصادها من المنافسة وسيطرة الدول المتقدمة . إن الهدف من هذا البحث هو تبيين أثر سعر الصرف على التجارة الخارجية الجزائرية، فتسوية المبادلات التجارية للدولة تتم باليورو والدولار ( تسديد مدفوعتها واستلام مقبوضاتها ) ، لذا فإن سعر الصرف بينهما يؤثر على التجارة الخارجية في الجزائر لذلك تم التطرق إلى دراسة أثر تقلب سعر صرف الدولار مقابل اليورو على صادرات الجزائر ووارداتها ومن ثم الآثار على الميزان التجاري وهذا في ظل تذبذب أسعار البترول . Abstract :   The exchange rate represents one of the most important variable affecting the foreign trade in different nations, the international economic change put a lot of countries especially the developing ones in front of a lot of challenges forcing them to review their fiscal and monetary policies and to adapt these policies to the various fluctuations occurring in the international area, protecting their economy from competition and control of developped countries. The purpose of this research is to identify the impact of the exchange rate on the Algerian foreign trade, and since Algeria uses both «euro» and «dollar» in settlements of its trade, the exchange rate between them affect its external (foreign) trade, that’s why it was adressed to study the impact of «dollar» volatility as an exchange rate against the «euro» on Algerian exports and imports and also on trade balance, this is in light of the fluctuation of oil prices.